2022
DOI: 10.1155/2022/3704987
|View full text |Cite
|
Sign up to set email alerts
|

A Multiparametric Fusion Radiomics Signature Based on Contrast-Enhanced MRI for Predicting Early Recurrence of Hepatocellular Carcinoma

Abstract: Objectives. The postoperative early recurrence (ER) rate of hepatocellular carcinoma (HCC) is 50%, and no highly reliable predictive tool has been developed yet. The aim of this study was to develop and validate a predictive model with radiomics analysis based on multiparametric magnetic resonance (MR) images to predict early recurrence of HCC. Methods. In total, 302 patients (training dataset: n = 211; validation dataset: n = 91) with pathologically confirmed HCC who underwent preoperative MR imaging were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The process of literature search and study selection is presented in Figure 1 . After screening according to the pre-defined inclusion/exclusion criteria, a total of 15 publications were identified for this meta-analysis, consisting of six radiomics studies based on CT and nine radiomics studies based on MRI ( 7 , 9 , 10 , 13 , 14 , 19 28 ). Most of the studies included in the analysis were retrospective, and all of them were published between 2017 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of literature search and study selection is presented in Figure 1 . After screening according to the pre-defined inclusion/exclusion criteria, a total of 15 publications were identified for this meta-analysis, consisting of six radiomics studies based on CT and nine radiomics studies based on MRI ( 7 , 9 , 10 , 13 , 14 , 19 28 ). Most of the studies included in the analysis were retrospective, and all of them were published between 2017 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous studies have utilized CT/MRI-based radiomics to predict ER after radical treatment, achieving high predictive value ( 7 , 9 , 10 , 13 , 14 ). However, the reported results seem quite variable due to the fact that these above studies differed in the diagnostic performance of the preoperative evaluation of ER because the differences in imaging modalities, research methods, sample size, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Early fusion is also known as data-level fusion and is the fusion of multiple modalities’ information before a feature input classifier is implemented [ 171 ]. Li et al [ 172 ] combined the MR image features of different sequences to construct radiomics signatures and then combined these with clinic-radiological risk factors to develop a multi-factor model based on a training set. They found that the multi-factor model had the highest performance.…”
Section: Ai-driven Radiomics Studiesmentioning
confidence: 99%
“…34 Therefore, nomograms based on CT or MRI features were also used in the study of prognosis of liver cancer, such as homogeneous signal, rim enhancement, peritumoral enhancement, and fusion radiomic signature. [35][36][37] https://doi.org/10.2147/JHC.S417123…”
Section: Risk Factors Included In Nomograms Clinical Characteristicsmentioning
confidence: 99%